2022
DOI: 10.1155/2022/6813421
|View full text |Cite
|
Sign up to set email alerts
|

The Multiple Pharmacologic Functions and Mechanisms of Action of Guizhi Fuling Formulation

Abstract: Objectives. Guizhi Fuling Formulation (GZFL), a traditional Chinese medical formulation, consists of Cinnamomi Ramulus, Paeoniae Radix Alba (or Paeoniae Radix Rubra), Moutan Cortex, Persicae Semen, and Poria, with multiple therapeutic functions such as sedation, antitumor activity, anti-inflammation, and neuroprotection. However, its clinical applications remain relatively fragmented, and the underlying mechanisms of GZFL in different diseases are still not very certain. Further research and summary in both ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 105 publications
0
2
0
Order By: Relevance
“…Previous animal experiment has demonstrated that GZFL could exert a signi cant anti-in ammatory effect by reducing the serum TNF-α levels and improving IL-10 and corresponding receptors levels, and could thus improve the recovery of rats with cerebral ischemia-reperfusion injury (Li et al 2007). Furthermore, multiple clinical evidence also supported that GZFL has signi cant bene ts for patients with cerebral ischemic injury by improving endothelial function, reducing cell apoptosis, and decreasing intracellular calcium ion levels (Chen et al 2016;Zhang et al 2017;Hu et al 2020;Gao et al 2022). While numerous animal experiments and clinical trials have proofed that GZFL holds promise as a potential therapeutic drug for IS, further research is necessary to investigate its clinical e cacy and potential pharmacological mechanisms in the treatment of IS.…”
Section: Introductionmentioning
confidence: 98%
“…Previous animal experiment has demonstrated that GZFL could exert a signi cant anti-in ammatory effect by reducing the serum TNF-α levels and improving IL-10 and corresponding receptors levels, and could thus improve the recovery of rats with cerebral ischemia-reperfusion injury (Li et al 2007). Furthermore, multiple clinical evidence also supported that GZFL has signi cant bene ts for patients with cerebral ischemic injury by improving endothelial function, reducing cell apoptosis, and decreasing intracellular calcium ion levels (Chen et al 2016;Zhang et al 2017;Hu et al 2020;Gao et al 2022). While numerous animal experiments and clinical trials have proofed that GZFL holds promise as a potential therapeutic drug for IS, further research is necessary to investigate its clinical e cacy and potential pharmacological mechanisms in the treatment of IS.…”
Section: Introductionmentioning
confidence: 98%
“…Paeoniae Radix Rubra (PRR, also known as Chishao) is a type of Chinese herbal medicine, which is the dried root of Paeonia lactiflora Pall. PRR is often used in TCM formulations to clinically treat cancer ( 9 , 10 ), such as the Guizhi Fuling Formulation ( 11 ) for the treatment of bladder cancer, OC and breast cancer. Paeoniflorin has been identified as one of the main components in PRR with antitumor activity ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…GFP is composed of Guizhi (GZ), Fuling (FL), Mudanpi (MDP), Chishao (CS), and Taoren (TR), and it exhibits a diverse range of pharmacological effects, including improving blood circulation, inhibiting platelet aggregation, and having anti-inflammatory properties. [15,16] However, the precise mechanism by which GFP exerts its therapeutic effects in the management of CSA remains unclear.…”
Section: Introductionmentioning
confidence: 99%